Is urinary 5-HIAA determination a valuable method in diagnosis of acute appendicitis in children? - Ozel, S.K.; Ilhan, N.; Kazez, A.; Apak, S.; Ilhan, N. (Medknow Publications and Media Pvt. Ltd, 2006)
The aim of the study is to investigate the significance of spot urine 5-hydroxyindoleacetic acid (5-HIAA) levels in patients admitted with the suspicion of acute appendicitis. Seventy-one patients with the mean age of 9.4±2.9 years, who were admitted to our pediatric surgery clinic between August 2002 and March 2004 with the complaints of abdominal pain were evaluated prospectively. Additionally spot urine samples were collected from 34 healthy children for control. 5-HIAA was detected from the urine samples in all children with high-performance liquid chromatography (HPLC) method. The results were analyzed with one way analysis of variance (ANOVA), post hoc Tukey HSD test and receiver operating characteristic (ROC) curve. After the clinical follow-up appendicitis was detected in 40 patients and abdominal pain was found to be due to causes other than appendicitis in 31 patients. Results were found to be correlative with the final diagnosis in all patients. The mean 5-HIAA levels were 2.5±1.8 ?mol/dl in healthy children, whereas 9±5 ?mol/dl in nonappendicitis and 18.9±17.8 ?mol/dl in appendicitis patients, respectively. The difference between the patients with acute appendicitis and the other two groups were statistically significant (P = 0.001). For a value of 8.9 ?mol/dl, this test was found to be 70% sensitive and 67% specific according to the ROC curve. 5-HIAA significantly rises in pediatric acute appendicitis. However, due to high values of SD and relatively low sensitivity and specificity, this test seems to have limited diagnostic power as a single parameter in childhood acute appendicitis.
Keywords: 5-HIAA; Acute appendicitis; Children; Diagnosis; Enterochromaffin cells